Casting a Wider Net on Ocean NETs - Cox, Emily; Boettcher, Miranda; Spence, Elspeth; Bellamy, Rob (Frontiers in Climate, 2021)
Societal issues involving policies and publics are generally understudied in research on ocean-based Negative Emission Technologies (NETs), yet will be crucial if novel techniques are ever to function at scale. Public attitudes are vital for emerging technologies: publics influence political mandates, help determine the degree of uptake by market actors, and are key to realizing broader ambitions for robust decision-making and responsible incentivization. Discourses surrounding ocean NETs will also have fundamental effects on how governance for the techniques emerges, shaping how they are defined as an object of governance, who is assigned the authority to govern, and what instruments are deemed appropriate. This Perspective brings together key insights on the societal dimensions of ocean NETs, drawing on existing work on public acceptability, policy assessment, governance, and discourse. Ocean iron fertilization is the only ocean NET on which there exists considerable social science research thus far, and we show that much evidence points against its social desirability. Taken in conjunction with considerable natural science uncertainties, this leads us to question whether further research is actually necessary in order to rule out ocean iron fertilization as an option. For other ocean NETs, there is a need for further research into social dimensions, yet research on analogous technologies shows that ocean interventions will likely evoke strong risk perceptions, and evidence suggests that the majority of ocean NETs may face a greater public acceptability challenge than terrestrial NETs. Ocean NETs also raise complex challenges around governance, which pose questions well-beyond the remit of the natural sciences and engineering. Using a conceptual exploration of the ways in which different types of discourse may shape emerging ocean NETs governance, we show that the very idea of ocean NETs is likely to set the stage for a whole new range of contested futures.